Molecular Dynamics Study on Lubrication Mechanism in Crystalline Structure between Copper and Sulfur. (26th October 2015) - Saitoh, Ken-ichi; Sato, Tomohiro; Takuma, Masanori; Takahashi, Yoshimasa; Chin, Ryuketsu
Abstract : To clarify the nanosized mechanism of good lubrication in copper disulfide (Cu2 S) crystal which is used as a sliding material, atomistic modeling of Cu2 S is conducted and molecular dynamics (MD) simulations are performed in this paper. The interatomic interaction between atoms and crystalline structure in the phase of hexagonal crystal of Cu2 S are carefully estimated by first-principle calculations. Then, approximating these interactions, we originally construct a conventional interatomic potential function of Cu2 S crystal in its hexagonal phase. By using this potential function, we perform MD simulation of Cu2 S crystal which is subjected to shear loading parallel to the basal plane. We compare results obtained by different conditions of sliding directions. Unlike ordinary hexagonal metallic crystals, it is found that the easy-glide direction does not always show small shear stress for Cu2 S crystal. Besides, it is found that shearing velocity affects largely the magnitude of averaged shear stress. Generally speaking, higher velocity results in higher resistance against shear deformation. As a result, it is understood that Cu2 S crystal exhibits somewhat liquid-like (amorphous) behavior in sliding condition and shear resistance increases with increase of sliding speed.